Preparation method and application of functional current collector with low thermal shrinkage and high tensile strength

By adding a high-entropy alloy heat shrink transition layer between the metal layer of the current collector and the base film, the deformation problem caused by heat shrinkage in the current collector in circulation applications is solved, and its tensile strength is improved, achieving higher battery cycle life and safety performance.

CN119864424AActive Publication Date: 2025-04-22YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD

Patent Information

Application Number
CN202510353261.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

In circulation applications, existing current collectors are prone to deformation due to heat shrinkage, which reduces the energy density and cycle life of the battery. At the same time, their tensile strength is insufficient, which affects performance.

Method used

A heat shrink transition layer was added between the metal layer and the base film. The material was a high-entropy alloy. The heat shrink transition layer and the copper layer were plated through magnetron sputtering process, and the copper layer was thickened by water plating to form a functional current collector with low heat shrinkage and high tensile strength.

Benefits of technology

It effectively reduces the thermal shrinkage deformation of the functional current collector, improves its deformation resistance and mechanical strength, extends the cycle life of the battery and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864424A_ABST
    Figure CN119864424A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a preparation method and application of a functional current collector with low thermal shrinkage and high tensile strength. The functional current collector is prepared by sequentially carrying out magnetron sputtering on the thermal shrinkage transition layer and the copper layer on the surface of the base film and then carrying out water plating on the copper layer. The functional current collector prepared by the invention can effectively solve the problems of relatively large thermal deformation and relatively large residual stress of the functional current collector, and also can improve the overall strength and stability of the functional current collector, so that the functional current collector has a wide application prospect in the technical field of batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a preparation method and application of a functional current collector with low thermal shrinkage and high tensile strength. Background Art

[0002] With the rapid development of new energy and electronic technology, the cycle life, safety performance, energy density, etc. of batteries have become top priorities. As a very important part of the battery, the current collector is used to collect the current generated by the active materials of the battery in order to form a larger current output. Its performance will directly affect the cycle life, energy density, safety, etc. of the battery. At present, copper foil and aluminum foil are mostly used as current collectors for the positive and negative electrodes in lithium batteries and sodium batteries. Such current collectors have high cost and quality, which is not conducive to the control of battery costs and the improvement of energy density. In this regard, foil has obvious advantages over traditional foils. The foil current collector is usually a "sandwich" structure, with a polymer polymer layer on the inner layer and metal conductive layers on both sides. The current collector has a thinner metal layer on the surface and a lighter polymer layer inside, which can well reduce the overall weight of the current collector, thereby increasing the energy density of the lithium-ion battery; at the same time, the thinner metal layer on the surface of the current collector is easier to disconnect than the traditional foil current collector when the lithium-ion battery has thermal runaway, thereby isolating the connection between the active material and the current collector, and preventing the lithium-ion battery from continuing to have thermal runaway. However, although foil current collectors have the advantages of low cost and light weight, a large amount of heat will be generated during the battery cycle after the current collectors are processed by coating, hot pressing, etc. or made into finished batteries, which will cause the current collectors to shrink too much and cause large thermal deformation and volume changes, thus causing deformation of the membrane surface and shedding of the copper layer, which will seriously reduce the energy density and cycle life of the battery and bring safety problems to the battery. At the same time, the low tensile strength of the current collector will cause it to passively break during the subsequent manufacturing or application process, thus affecting the performance of the current collector.

[0003] In order to overcome the defects of the prior art, the present invention provides a preparation method and application of a functional current collector with low thermal shrinkage and high tensile strength. Summary of the invention

[0004] The object of the present invention is to provide a preparation method and application of a functional current collector with low thermal shrinkage and high tensile strength to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A functional current collector with low heat shrinkage and high tensile strength comprises a base film, a heat shrinkage transition layer formed on the surface of the base film and a metal layer formed on the surface of the heat shrinkage transition layer; wherein the heat shrinkage rate of the heat shrinkage transition layer ranges between the metal layer and the base film, and the heat shrinkage rate of the heat shrinkage transition layer is less than the heat shrinkage rate of the base film.

[0006] Preferably, the material of the heat shrinkable transition layer is a high entropy alloy, specifically TaNbHfZrTi, TaNbHfZrTiMo 0.75 , MoNbTaTiV, AlMgLiZnCu, AlMgZnCuSi, AlZrTiNbMo, CoCrFeMnNi, NbMoTaWVCr, ZrTiHfV 0.5 Nb 0.5 C 0.2 , TaNbHfZrTiMoW, VNbMoTaW, Ti 4.8 Zr2H 1.5 AlNb 0.7 , any one of Ti3Al2V2Nb2Mo; wherein TaNbHfZrTi, MoNbTaTiV, AlMgLiZnCu, AlMgZnCuSi, AlZrTiNbMo, CoCrFeMnNi, NbMoTaWVCr, TaNbHfZrTiMoW, VNbMoTaW means that the mass ratio of each metal element is 1:1:1:1:1; TaNbHfZrTiMo 0.75 Indicates that the mass ratio of each metal element is 1:1:1:1:1:0.75; ZrTiHfV 0.5 Nb 0.5 C 0.2 The mass ratio of each metal element is 1:1:1:0.5:0.5:0.2; Ti 4.8 Zr2H 1.5 AlNb 0.7 It means that the mass ratio of each metal element is 4.8:2:1.5:1:0.7; Ti3Al2V2Nb2Mo means that the mass ratio of each metal element is 3:2:2:2:1.

[0007] Preferably, the metal layer is copper or a copper alloy.

[0008] Preferably, the base film is made of any one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polyether sulfone, polyethylene, polyvinyl chloride, polystyrene, polycarbonate, and polyvinylidene fluoride.

[0009] A method for preparing a functional current collector with low thermal shrinkage and high tensile strength comprises the following steps: S1: Take a base film, use a magnetron sputtering process to plate a heat shrink transition layer on the surface of the base film, and then use copper or copper alloy as a target material to magnetron sputter to plate a copper or copper alloy layer on the surface of the heat shrink transition layer; S2: thickening the copper or copper alloy layer of S1 by water plating to form a metal layer, thereby obtaining a functional current collector.

[0010] More optimally, in step S1, the thickness of the base film is 4.0-4.5 μm.

[0011] More optimally, in step S1, the thickness of the heat shrinkable transition layer is 5-15 nm.

[0012] More optimally, in step S1, the thickness of the copper or copper alloy layer is 60-70 nm.

[0013] More optimally, in step S2, the thickness of the copper or copper alloy thickened by water plating is 1-2 μm.

[0014] The battery prepared with the functional current collector with low thermal shrinkage and high tensile strength comprises a cathode, an anode, a shell and an electrolyte layer arranged between the cathode and the anode; wherein the cathode comprises a functional current collector and an active material layer.

[0015] Beneficial effects of the present invention: The present invention sequentially magnetron sputters a heat shrinkage transition layer and a copper layer on the surface of the base film, and then water-plates the copper layer to prepare a functional current collector. The present invention is characterized in that the present invention provides a low heat shrinkage and high tensile strength functional current collector, and the functional current collector is added with a heat shrinkage transition layer between the metal layer and the inner polymer layer to reduce the heat shrinkage deformation of the functional current collector in cyclic applications, which can effectively solve the problem of large heat deformation and large residual stress of the functional current collector, and will not affect the conductivity of the functional current collector, and can also improve the overall strength and stability of the functional current collector.

[0016] Among them, the material of the heat shrink transition layer is a high entropy alloy, which has the following advantages: on the one hand, the composition of the high entropy alloy contains a variety of high melting point metals, which makes it have a high melting point and thermal stability. During the processing of magnetron sputtering, the functional current collector will not be greatly deformed due to heating or cooling. After the processing is completed, the film layer of the functional current collector will not be deformed or fall off due to residual stress during the application process. On the other hand, due to its uniformly mixed atomic structure and the joint action of multiple groups of elements, the high entropy alloy has a high deformation resistance and mechanical strength. It can withstand greater external tensile or compressive forces without plastic deformation, which helps to reduce the deformation and improve the tensile strength of the functional current collector. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 is a structural diagram of a functional current collector of the present invention; In the figure: 1: base film, 2: heat shrinkable transition layer, 3: metal layer. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Source of raw materials: Polypropylene film: provided by Anhui Tongfeng Electronics Co., Ltd., model MRPP; AlMgLiZnCu, a target material provided by Lavoisier (Beijing) New Materials Technology Co., Ltd.; AlZrTiNbMo, a target material provided by Plansee SE; CoCrFeMnNi, a target material provided by Plansee SE; ZrTiHfV 0.5 Nb 0.5 C 0.2 , is the target material provided by Lavoisier (Beijing) New Material Technology Co., Ltd.; Ti3Al2V2Nb2Mo, is the target material provided by Baoji Lihua Metal Materials Co., Ltd.; Cr20Ni80, is the target material provided by Lavoisier (Beijing) New Material Technology Co., Ltd.

[0020] Embodiment 1: S1: A 4.5 μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (AlMgLiZnCu layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material to magnetron sputter a copper layer on the surface of the heat shrinkable transition layer 2; wherein the thickness of the heat shrinkable transition layer 2 (AlMgLiZnCu layer) is 10 nm, and the thickness of the copper layer is 60 nm; the magnetron sputtering process is as follows: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5 Pa, the power is 10 KW, and a 10 nm thick AlMgLiZnCu layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; then the copper target power is set to 15 KW, and a 60 nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0021] Embodiment 2: The heat shrinkable transition layer 2 (AlMgLiZnCu layer) is replaced by the AlZrTiNbMo layer, and the rest is the same as Embodiment 1, and the specific steps are as follows: S1: A 4.5 μm polypropylene film is used as the base film 1, and a heat shrinkable transition layer 2 (AlZrTiNbMo layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material, and a copper layer is plated on the surface of the heat shrinkable transition layer 2 by magnetron sputtering; wherein the thickness of the heat shrinkable transition layer 2 (AlZrTiNbMo layer) is 10 nm, and the thickness of the copper layer is 60 nm; the magnetron sputtering process is: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5 Pa, the power is 10 KW, and a 10 nm thick AlZrTiNbMo layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; then the copper target power is set to 15 KW, and a 60 nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0022] Embodiment 3: The heat shrinkable transition layer 2 (AlMgLiZnCu layer) is replaced by a CoCrFeMnNi layer, and the rest is the same as Embodiment 1, and the specific steps are as follows: S1: A 4.5 μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (CoCrFeMnNi layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material, and a copper layer is plated on the surface of the heat shrinkable transition layer 2 by magnetron sputtering; wherein the thickness of the heat shrinkable transition layer 2 (CoCrFeMnNi layer) is 10 nm, and the thickness of the copper layer is 60 nm; the magnetron sputtering process is: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5 Pa, the power is 10 KW, and a 10 nm thick CoCrFeMnNi layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; then the copper target power is set to 15 KW, and a 60 nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0023] Example 4: Replacing the heat shrinkable transition layer 2 (AlMgLiZnCu layer) with ZrTiHfV 0.5 Nb 0.5 C 0.2 The rest is the same as in Example 1, and the specific steps are as follows: S1: a 4.5 μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (ZrTiHfV 0.5 Nb 0.5 C 0.2 layer), and then copper is used as a target material to magnetron sputter a copper layer on the surface of the heat shrink transition layer 2; wherein the heat shrink transition layer 2 (ZrTiHfV 0.5 Nb 0.5 C 0.2 The thickness of the copper layer is 60nm, and the magnetron sputtering process is as follows: the base film temperature is maintained at -20℃, the sputtering pressure is maintained at 0.5Pa, the power is 10KW, and a 10nm thick ZrTiHfV is plated on the upper and lower surfaces of the base film at a speed of 4m / min. 0.5 Nb 0.5 C 0.2 Then set the copper target power to 15KW, and plate a 60nm thick copper layer on the upper and lower surfaces of the base film at a speed of 4m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0024] Example 5: The heat shrinkable transition layer 2 (AlMgLiZnCu layer) is replaced by a Ti3Al2V2Nb2Mo layer. The rest is the same as Example 1. The specific steps are as follows: S1: A 4.5 μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (Ti3Al2V2Nb2Mo layer) is plated on the surface of the base film 1 by a magnetron sputtering process. Then, copper is used as a target material to magnetron sputter a copper layer on the surface of the heat shrinkable transition layer 2; wherein the heat shrinkable transition layer 2 ( The thickness of the Ti3Al2V2Nb2Mo layer is 10nm, and the thickness of the copper layer is 60nm; the magnetron sputtering process is: the base film temperature is maintained at -20℃, the sputtering gas pressure is maintained at 0.5Pa, the power is 10KW, and a 10nm thick Ti3Al2V2Nb2Mo layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; then the copper target power is set to 15KW, and a 60nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0025] Embodiment 6: The thickness of the heat shrinkable transition layer 2 (AlMgLiZnCu layer) is modified to 5nm, and the rest is the same as Embodiment 1, and the specific steps are as follows: S1: A 4.5μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (AlMgLiZnCu layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material, and a copper layer is plated on the surface of the heat shrinkable transition layer 2 by magnetron sputtering; wherein the thickness of the heat shrinkable transition layer 2 (AlMgLiZnCu layer) is 5nm, and the thickness of the copper layer is 60nm; the magnetron sputtering process is: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5Pa, the power is 10KW, and a 5nm thick AlMgLiZnCu layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; then the copper target power is set to 15KW, and a 60nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0026] Embodiment 7: The thickness of the heat shrinkable transition layer 2 (AlMgLiZnCu layer) is modified to 15 nm, and the rest is the same as Embodiment 1, and the specific steps are as follows: S1: A 4.5 μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (AlMgLiZnCu layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material, and a copper layer is plated on the surface of the heat shrinkable transition layer 2 by magnetron sputtering; wherein the thickness of the heat shrinkable transition layer 2 (AlMgLiZnCu layer) is 15 nm, and the thickness of the copper layer is 60 nm; the magnetron sputtering process is: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5 Pa, the power is 10 KW, and a 15 nm thick AlMgLiZnCu layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; then the copper target power is set to 15 KW, and a 60 nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4 m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0027] Comparative Example 1: The heat shrinkage transition layer 2 (AlMgLiZnCu layer) was removed, and the rest was the same as Example 1, and the specific steps were as follows: S1: A 4.5 μm polypropylene film was used as a base film 1, and copper was used as a target material, and a copper layer was plated on its surface by magnetron sputtering; the thickness of the copper layer was 60 nm; the magnetron sputtering process was: the base film temperature was maintained at -20°C, the sputtering gas pressure was maintained at 0.5 Pa, the copper target power was set to 15 KW, and a 60 nm thick copper layer was plated on the upper and lower surfaces of the base film at a speed of 4 m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a current collector; wherein the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the electroplating solution, wherein the electroplating solution is composed of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and a copper plating additive; the copper plating additive includes 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0028] Comparative Example 2: The heat shrinkable transition layer 2 (AlMgLiZnCu layer) is replaced by a Cr20Ni80 layer, and the rest is the same as Example 1, and the specific steps are as follows: S1: A 4.5μm polypropylene film is used as a base film 1, and a heat shrinkable transition layer 2 (Cr20Ni80 layer) is plated on the surface of the base film 1 by a magnetron sputtering process, and then copper is used as a target material to magnetron sputter a copper layer on the surface of the heat shrinkable transition layer 2; wherein the thickness of the heat shrinkable transition layer 2 (Cr20Ni80 layer) is 10nm, and the thickness of the copper layer is 60nm; the magnetron sputtering process is: the base film temperature is maintained at -20°C, the sputtering gas pressure is maintained at 0.5Pa, the power is 10KW, and a 10nm thick Cr20Ni80 layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; then the copper target power is set to 15KW, and a 60nm thick copper layer is plated on the upper and lower surfaces of the base film at a speed of 4m / min; S2: The copper layer surface of S1 is thickened by water plating to form a metal layer 3 to obtain a functional current collector; the thickness of the water-plated thickened copper is 1 μm; the water plating process is: the film material with the sputtered copper layer is placed in a water plating tank with a constant temperature of 22°C of the plating solution, wherein the plating solution consists of 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, and copper plating additives; the copper plating additives include 20 mg / L sodium polydisulfide dipropane sulfonate and 200 mg / L polyethylene glycol, and the molecular weight of the polyethylene glycol is 8000.

[0029] Detection test:

[0030] Tensile strength test: The finished product prepared by the present invention is used as a sample, and the tensile strength of the sample is measured using an MTS Criterion 42 tensile testing machine. Parameter setting: The clamp spacing on the tensile testing machine is 100 mm, the test speed is 225 mm / min, and the tensile strength is obtained by testing.

[0031] Thermal shrinkage test: The finished product prepared by the present invention is used as a sample, and the thermal shrinkage of the sample is measured using the RSY-01 film thermal shrinkage tester. Parameter setting: The sample is quickly immersed in the medium of a 142°C constant temperature bath and the timing is started. During the test, the sample is kept evenly heated and shrinks freely. After 20 seconds, the sample is taken out and immersed in a normal temperature bath medium for cooling. After cooling for 5 seconds, it is taken out and left horizontally for 10 minutes. The thermal shrinkage is obtained by testing. The results are shown in the following table:

[0032] Conclusion: By adding a heat-shrinkable transition layer, the thermal shrinkage deformation of the functional current collector in cyclic applications can be effectively reduced, and the problems of large thermal deformation and large residual stress of the functional current collector can be solved, thereby improving the cycle life and safety performance of the battery; in addition, by adding a heat-shrinkable transition layer, the deformation resistance and mechanical strength of the functional current collector can be effectively improved, thereby improving the strength of the battery's service life.

[0033] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A functional current collector with low thermal shrinkage and high tensile strength, characterized in that: It comprises a base film (1), a heat shrinkable transition layer (2) formed on the surface of the base film (1), and a metal layer (3) formed on the surface of the heat shrinkable transition layer (2); wherein the heat shrinkage rate of the heat shrinkable transition layer (2) is within the range between the metal layer (3) and the base film (1), and the heat shrinkage rate of the heat shrinkable transition layer (2) is less than the heat shrinkage rate of the base film (1); The material of the heat shrinkable transition layer (2) is a high entropy alloy, specifically TaNbHfZrTi, TaNbHfZrTiMo 0.75 , MoNbTaTiV, AlMgLiZnCu, AlMgZnCuSi, AlZrTiNbMo, CoCrFeMnNi, NbMoTaWVCr, ZrTiHfV 0.5 Nb 0.5 C 0.2 , TaNbHfZrTiMoW, VNbMoTaW, Ti 4.8 Zr2H 1.5 AlNb 0.7 , any one of Ti3Al2V2Nb2Mo.

2. A functional current collector with low thermal shrinkage and high tensile strength according to claim 1, characterized in that: The metal layer (3) is copper or a copper alloy.

3. A functional current collector with low thermal shrinkage and high tensile strength according to claim 1, characterized in that: The base film (1) is made of any one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polyether sulfone, polyethylene, polyvinyl chloride, polystyrene, polycarbonate and polyvinylidene fluoride.

4. A method for preparing a functional current collector with low thermal shrinkage and high tensile strength according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: taking a base film (1), using a magnetron sputtering process to plate a heat shrinkable transition layer (2) on the surface of the base film (1), and then using copper or a copper alloy as a target material to magnetron sputter plate a copper or a copper alloy layer on the surface of the heat shrinkable transition layer (2); S2: The copper or copper alloy layer of S1 is plated with water to thicken the copper or copper alloy to form a metal layer (3) to obtain a functional current collector.

5. The method for preparing a functional current collector with low thermal shrinkage and high tensile strength according to claim 4, characterized in that: In step S1, the thickness of the base film (1) is 4.0-4.5 μm.

6. The method for preparing a functional current collector with low thermal shrinkage and high tensile strength according to claim 4, characterized in that: In step S1, the thickness of the heat shrinkable transition layer (2) is 5-15 nm.

7. The method for preparing a functional current collector with low thermal shrinkage and high tensile strength according to claim 4, characterized in that: In step S1, the thickness of the copper or copper alloy layer is 60-70 nm.

8. The method for preparing a functional current collector with low thermal shrinkage and high tensile strength according to claim 4, characterized in that: In step S2, the copper or copper alloy is thickened by water plating to a thickness of 1-2 μm.

9. A battery prepared with a functional current collector having low thermal shrinkage and high tensile strength according to any one of claims 1 to 3, characterized in that: It includes a cathode, an anode, a shell, and an electrolyte layer arranged between the cathode and the anode; The cathode includes a functional current collector and an active material layer.

Citation Information

Patent Citations

  • Composite current collector and preparation method thereof, lithium ion battery and vehicle

    CN114597418A

  • Corrosion-resistant composite current collector and preparation method thereof

    CN118263447A

  • Composite current collector and preparation method thereof

    CN119040832A

  • Metal lithium negative electrode high-entropy current collector and preparation method and application thereof

    CN119400810A

  • Composite current collector

    CN119650709A

Cited By

  • Processing method of functional current collector, functional current collector prepared by applying processing method and secondary battery

    CN120072821A

  • A processing method of a functional set fluid, a functional set fluid prepared by applying the method, and a secondary battery

    CN120072821B

  • Preparation method of adhesive magnetic control deformation film suitable for multi-structure surface

    CN120775240A